Caracterización molecular de los virus que afectan al maracuyá (Passiflora edulis Sims) y otras passifloras en Colombia - Morales, Francisco José; Lozano Potes, Iván; Muñoz, C.; Castaño Zapata, M.; Arroyave, José A.; Varón de Agudelo, Francia; Chavez, B.; Castillo, G.P. (2001)
The main passionfruit production areas in 11 departments of Colombia, were surveyed and a total of 338 samples collected from diseased passionfruit plants. Samples were examined by electron microscopy, serology, ADNc amplification, cloning and sequencing of viral nucleic acids. The survey and analyses conducted, demonstrated the existence of two different viruses . The prevalent viral pathogen in all departments surveyed, was a species of the Potyvirus genus. An isolate of this potyvirus from Roldanillo, Valle, was cloned and partially sequenced, demonstrating a high nucleotide sequence identity (97%) with Soybean mosaic virus (SMV). The second virus, detected only in the departments of Valle, Antioquia and Santander, was shown to be a distinct species of the Tymovirus genus (60-76% homology with tymoviruses characterized at the molecular level). However, this virus was antigenically related to Passion fruit yellow mosaic virus, a tymovirus that induces similar symptoms in passionfruit in Brazil. Consequently, this name will be retained for the Colombian tymovirus until an isolate of the Brazilian tymovirus is characterized at the molecular level. The possibility of producing virus-free planting material of commercial passionfruit varieties, coincides with the need to increase passionfruit production in Colombia in order to meet the increasing internal and external demand for these fruits and their products.